The crosstalk effect between ferrous and other ions metabolism in ferroptosis for therapy of cancer - Ke, Kun; Li, Li; Lu, Chao; Zhu, Qicong; Wang, Yuanyu; Mou, Yiping; Wang, Huiju; Jin, Weiwei (Frontiers in Oncology, 2022)
Ferroptosis is a special type of cell death, which is characterized by excessive accumulation of reactive oxygen species and lipid peroxidation. Elucidation of ferroptosis pathways may lead to new cancer therapies. With the further research, the mechanism of ferroptosis can be summarized as oxidation and antioxidant mechanisms. In this process, ferrous ions play a crucial role in the cellular oxidation, plasma membrane damage, reactive oxygen species removal imbalance and lipid peroxidation. Yet, deregulation of intracellular cations (Fe2+, Ca2+, Zn2+, etc.) and anions (Cl-, etc.) have been widely reported to be involved in ferroptosis, while their specific regulatory mechanisms have not been established. To further understand the crosstalk effect between ferrous and other ions in ferroptosis, we reviewed the ferroptosis process from the perspective of ions metabolism.